Empowering limited-resource countries: collaborating with expert centers for diagnosis of primary ciliary dyskinesia - Yuksel Kalyoncu, Mine; Hjeij, Rim; Yanaz, Muruvvet; Gulieva, Aynur; Selcuk Balcı, Merve; Karabulut, Şeyda; Metin Cakar, Neval; Ergenekon, Almala Pınar; Erdem Eralp, Ela; Gokdemir, Yasemin; Omran, Heymut; Karadag, Bülent Taner (Frontiers in Molecular Biosciences, 2025)
IntroductionPrimary ciliary dyskinesia (PCD) is an autosomal recessive rare disease caused by alterations in ciliary structure and function. Without a unique gold standard diagnostic test, the European Respiratory Society and the American Thoracic Society recommend using various diagnostic techniques to improve accuracy. This study aimed to demonstrate the effectiveness of immunofluorescence (IF) analysis in the diagnosis of PCD cases with uncertain genetic results and to demonstrate the importance of international collaboration in the diagnosis of PCD.MethodsIn collaboration with IF specialists at the University of Münster, individuals with inconclusive results in the Marmara University PCD panel consisting of the 22 most common genes and clinically suggestive of PCD were included in the study. IF imaging determined the subcellular localization of DNAH5 and GAS8 in respiratory epithelial cells. Nasal nitric oxide measurements, high-speed video microscopy (HSVM) analysis, and genetic analyses were performed.Results19 patients were evaluated. The median age (25–75p) was 15 years (10–20 years) with 12 (63.2%) males. Three cases (15.7%) showed an absence of DNAH5, and one (5.3%) had a proximal distribution of DNAH5 in the ciliary axoneme. One case (5.3%) had cells without cilia, indicating a possible ciliogenesis defect. All individuals with abnormal IF analysis had a PICADAR score of 6 or above, and their cilia were immotile in HSVM.DiscussionConsistent with the IF finding suggesting a ciliogenesis defect, further genetic analysis revealed biallelic pathogenic variants in CCNO in the affected individual. The absence of DNAH5 in the respiratory epithelial cells of an individual carrying heterozygous pathogenic splice variants in DNAH5 suggests the need for further genetic analysis. This study underscores the importance of international collaboration in diagnosing rare diseases like PCD.